Sintesa Konsep Spiritual Leadership dan Islamic Leadership - Abi Sopyan Febrianto (Coopetition : Jurnal Ilmiah Manajemen, 2020)
Spiritual leadership and Islamic leadership are considered to be the same thing frequently, but in reality illustrate differently. Spiritual leadership emphasizes the quality of relationships and the role of leaders in their organizations, while Islamic leadership focuses more on the characteristics of a leader. It is important to make a conceptual article that examines the differences between the two and synthesizes, so that the results are found with a more thorough concentration. This article attempts to synthesize spiritual leadership theory according to Fry (2003) and Islamic leadership according to Antonio (2013) and Nuruddin (2011). The results of the synthesis theories give a more moderate and comprehensive understanding.